LIFE CYCLE ASSESSMENT: A COMPARISON STUDY ON THE VARIOUS ELECTRONIC WASTE MANAGEMENT OPTION - Norazli, Othman; Nurul Aini, Osman; Shreeshivadasan, Chelliapan; Roslina, Mohammad (2017)
Electronic waste is a global issue either to developed or developing countries. The difference between each country is only in their ways to encounter the electronic waste problem through management and legislation. The end of electric and electronic equipment lives will pose a significant amount of problems to the environment and human health if the waste generated is not properly treated. The study aims to evaluate the best management practice (BMPs) for electronic waste management through the simulation study using life cycle assessment tool to measure the environmental impact of various electronic waste management options. Three types of management scenarios are considered in this study. For scenario 1, landfill technology consists of management options according to the order starting with collecting and transporting wastes and finally, disposing the wastes at the landfill. Scenario 2 represents recycling technology that consists of management options according to the order, starting with collecting, transporting, and recycling wastes, and waste central sorting, and finally, disposing the waste at the landfill. Scenario 3 represents integrated technology that consists of management options according to the order, starting with collecting, transporting, and recycling wastes, waste central sorting, and thermal treatment (convert waste to energy), and finally, disposing the waste at the landfill. The result of the study showed that based on the balance between saving the world's source of energy and raw materials and impact to the environment, the electronic waste management options that will give minimum impact to the environment and able to save the world's source of energy and raw materials are integrated technology, followed by recycling technology, and lastly landfill technology. The finding of the study will assist the local authorities in the formulation of the most efficient and effective options for managing electronic waste in a sustainable manner.